Industrial Applications of Ionic Liquids - Mutelet, Fabrice (IntechOpen, 2023)
Due to their very low volatility, high thermal stability, and ability to dissolve a wide variety of compounds, ionic liquids appear to meet the rigorous criteria for industrial applications. Among other uses, ionic liquids appear to be efficient for gas capture, biomass pretreatment, separation problems, and electrochemistry. They are also used in electrolytes, as lubricants, catalysts, or as antistatic agents. This book discusses the various uses of ionic liquids. Chapters discuss such topics as the use of ionic liquids in batteries, new mono, di, and trimeric imidazolium and pyridinium ionic liquids as catalysts in organic chemistry, the physico-chemical properties of ionic liquid-substituted double-network gels for industrial applications, the use of paramagnetic ionic liquids in magnetic resonance imaging, the compatibility of filter materials used with ionic liquids, and the development of low-friction ion gels for industrial applications.